Whatever happened to Sequence of Tense? - Laca, Brenda (Revista Letras, 2019)
This paper addresses apparent violations of Sequence of Tense in subjunctive clauses in some Spanish varieties. We show that the coexistence of simultaneous interpretations for the past and the present subjunctive under a matrix past invalidates a crucial prediction of some theories of Sequence of Tense. We then conduct a corpus-based investigation of the [present under past]- pattern in indicative and subjunctive complement clauses in Argentinian Spanish, whose results indicate that there are two distributionally and semantically distinct manifestations of this pattern, one involving indicative and polarity subjunctive clauses, the other involving intensional and factive subjunctive clauses. This provides further evidence in favor of Quer’s (1998, 2006, 2016) hypothesis as to the central relevance of the divide between intensional and polarity subjunctives.